The Influence of Tiktok English Videos Toward Students’ Writing Skill in Analytical Exposition Text (A Quasi Experimental Study at the Eleventh Grade Students of SMAN 6 Serang) (Metakognisi, 2025)
The purpose of this study was to find out the influence of TikTok English videos on students' writing skills in analytical exposition texts at the eleventh grade of SMAN 6 Serang. The method of this study was a quasi-experimental design. The sample selected through purposive sampling, with 25 students in experimental and control class. The experimental group was taught using TikTok English videos, while the control group received conventional instruction. The results showed that the experimental group achieved a higher average post-test score (80.76) compared to the control group (75.16). The Independent Samples T-Test revealed a Sig. (2-tailed) value of